Maqashid Effect: Apakah Maqashid Syariah Membuat Muslim Bahagia ? Studi Kasus Data IFLS Gelombang 5 - Muhammad Afif Rifqi; Nurfala Safitri; Muhammad Abdul Rohman (Asyafina Akademik Press, 2022)
This study aims to determine how the influence of maqashid sharia on the happiness of the Muslim community in Indonesia, both in urban and rural areas in Indonesia. This study uses IFLS 2014 wave 5 data with the estimated logit model. The results of this study state that education (akal), health (jiwa), and income (maal) are significantly positively related to the possibility of the level of happiness of the Indonesian people not only in urban areas but also in rural areas.